The application of medical ethics in the developing countries - A neurosurgical perspective - Hossain, Iftakher; Hutchinson, Peter; Kawsar, Khandkar; Kolias, Angelos; dos Santos; Adriana Libório; Esene, Ignatius N.; Thango, Nqobile; Baticulon, Ronnie; Laki, Beata; Ammar, Ahmed (ELSEVIER, 2025)
Introduction: Neurosurgery is one of the rapidly evolving specialities of medical science, where the neurosurgeons have to provide evidence-based interventions in life threatening conditions maintaining the ethical standards.
Research question: This narrative review sheds light on the current hindrances of the ethical aspects of neurosurgical practice in low and middle-income countries (LMICs) and provide some feasible solutions for future.
Material and methods: A literature search was conducted using PubMed, Scopus and ISI web of knowledge focused on articles in English with the words "medical ethics" together with the words "neurosurgery", "ethical practice", "low and middle-income countries", "surgical innovation", "randomized clinical trials" and "outcome" alone or in combination.
Results: Due to the lack of neurosurgeons and essential infrastructures in LMICs, the practical application of medical ethics is more complicated in the field of neurosurgery. Main obstacles to conduct preclinical and clinical research in the LMICs are the lack of proper ethics committees, quality data, trained manpower and sufficient research funding. Implementation of randomized clinical trials (RCTs) is also difficult for the neurosurgeons working in LMICs.
Discussion and conclusion: To improve the situation, socio-economic development, including educating the citizens of these countries about their rights, functional regulatory bodies like medical and dental councils, teaching the neurosurgeons about the internationally recognized medical ethics, quality control regulations by the ministry of health and welfare, and more funding for the health care sectors are urgently needed. Global collaboration is needed to help the LMICs to provide their patients international but "customized" standard care.